Exercise training alters the genomic response to acute exercise in human adipose tissue. (August 2018) - Fabre, Odile; Ingerslev, Lars R; Garde, Christian; Donkin, Ida; Simar, David; Barrès, Romain
Aim: To determine the genomic mechanisms by which adipose tissue responds to acute and chronic exercise.Methods: We profiled the transcriptomic and epigenetic response to acute exercise in human adipose tissue collected before and after endurance training.Results: Although acute exercises were performed at same relative intensities, the magnitude of transcriptomic changes after acute exercise was reduced by endurance training. DNA methylation remodeling induced by acute exercise was more prominent in trained versus untrained state. We found an overlap between gene expression and DNA methylation changes after acute exercise for 32 genes pre-training and six post-training, notably at adipocyte-specific genes.Conclusion: Training status differentially affects the epigenetic and transcriptomic response to acute exercise in human adipose tissue.